The establishment of twelve island groups as a development directive in Maluku Province - Patrich P E Papilaya; I N S Jaya; Tri Rusolono (Tropical Small Island Agriculture Management, 2022)
This research was created to test the existence of the determination of twelve groups of development islands that are by the development of development in the field of forestry. Biophysical, social and economic data were used to test the twelve island clusters' determination. Cluster analysis is used in testing the determination of twelve island clusters. The kaiser-Meyer-Elkin (KME) and multicollinearity tests are used to obtain data quality in cluster analysis. The cluster analysis results using twelve variables free of multicollinearity (VIF) resulted in five island clusters. Cluster analysis using Ward's method with Kophenitic distance (Cophenetic Distance) provides maximum results, where the distance between the furthest groups (between classes) of 76028208246067.70 or 97.15% and the closest distance of fellow groups 2228914432702.33 or 2.85 %.